2014
DOI: 10.1177/2051415814551821
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in out-patients undergoing flexible cystoscopy for the investigation of bladder cancer

Abstract: Objectives: Flexible cystoscopy can cause patients significant psychological distress, especially when utilised in the diagnostic pathway for suspected bladder cancer. We aimed to assess the prevalence of general anxiety and depression, as well as procedure-related worry and pain in patients undergoing local anaesthetic flexible cystoscopy and to determine whether these conditions occur more frequently in subsets of the population. Patients and methods: Patients referred for flexible cystoscopy were invited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…This give privilege to female cancer patients to experience wide range of siege stressors more than males that affected them because of limited medication, difficulty in transfer and more problems related and lead to depressive symptoms among females. In addition, the current study results were consistent with the study of Ellis et al [14] found that the prevalence of was female and unmarried patients. Also, the results seem to be inconsistent with the results of Lubbad et al [23] that indicated significant differences between the means of depression according to sex in favor of males.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This give privilege to female cancer patients to experience wide range of siege stressors more than males that affected them because of limited medication, difficulty in transfer and more problems related and lead to depressive symptoms among females. In addition, the current study results were consistent with the study of Ellis et al [14] found that the prevalence of was female and unmarried patients. Also, the results seem to be inconsistent with the results of Lubbad et al [23] that indicated significant differences between the means of depression according to sex in favor of males.…”
Section: Discussionsupporting
confidence: 92%
“…Such findings may be due to continue siege the imposed by the Israel government on Gaza strip for long time period and reflected on the mental health of the cancer patients. However, Ellis et al [14] found that the prevalence of significant depression 3.5%. This was higher in younger, female and unmarried patients.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Flexible cystoscopy is an important diagnostic tool for the urologist and is used in an outpatient setting for patients who present with hematuria and LUTS, as well as in the diagnosis of bladder cancer, and important for surveillance of patients with known bladder cancer. 15 Investigations that directly assess prostatic anatomy allow the accurate diagnosis of restructuring before it significantly progresses, provide additional qualitative information on the state of healing, and help determine both the need for and the type of intervention. 16 However, the evidence for patients undergoing flexible cystoscopy in relation to LUTS in the long-term follow-up is absent and remains controversial.…”
Section: Introductionmentioning
confidence: 99%